The impact of sulfur functionalisation on nitrogen-based ionic liquid cations. Issue 81 (25th September 2018) - Santos, Ana R.; Hanson-Heine, Magnus W. D.; Besley, Nicholas A.; Licence, Peter
Abstract : XPS is used to investigate the impact of sulfur containing substituents on the electronic structure of a series of N-based cations, all with a common anion, [NTf2 ] − . The experimental data is complex and cannot be easily deconstructed, DFT provides critical insight into bonding and electronic structure for each system studied. Abstract : It has been demonstrated that bonding and interactions within ionic liquids (ILs) can be elegantly tuned by manipulation of structure and the introduction of functional groups. Here we use XPS to investigate the impact of sulfur containing substituents on the electronic structure of a series of N-based cations, all with a common anion, [NTf2 ] − . The experiments reveal complexity and perturbation of delocalised systems which cannot be easily interpreted by NMR and XPS alone, DFT provides critical insight into bonding and underpins the assignment of spectra and development of deconstruction models for each system studied.